2019
DOI: 10.1007/s10840-019-00631-x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of automated detection of sleep apnea using implantable pacemakers and defibrillators: a comparison with simultaneous polysomnography recording

Abstract: Purpose Sleep-related breathing disorders (SRBD) have been associated with adverse cardiovascular events and prognosis. Some modern pacemakers (PMK) and implantable cardioverter defibrillators (ICD) are equipped with thoracic impedance monitoring systems which allow detecting fluctuations in tidal volume occurring in SRBD. This study aimed at assessing the accuracy of a novel transthoracic impedance-based PMK/ICD sensor for automatic detection of SRBD.Methods We prospectively enrolled 31 consecutive patients s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…The safety and efficacy of RM was established a decade ago by the landmark TRUST trial, in which RM with automatic daily surveillance of ICD was able to detect actionable events more rapidly than conventional in‐office visits 15 . As also reported in several studies, not only does RM play a central role in preventing hospitalizations and improving survival and quality of life in patients with CIEDs, it is also a cost‐effective alternative to in‐person evaluations 16–25 . Overall, in the context of the COVID‐19 emergency, the improvement of RM coverage has facilitated continuous patient assistance and significantly reduced the risk of virus transmission among both more vulnerable populations and healthcare providers 26–28 …”
Section: Discussionmentioning
confidence: 97%
“…The safety and efficacy of RM was established a decade ago by the landmark TRUST trial, in which RM with automatic daily surveillance of ICD was able to detect actionable events more rapidly than conventional in‐office visits 15 . As also reported in several studies, not only does RM play a central role in preventing hospitalizations and improving survival and quality of life in patients with CIEDs, it is also a cost‐effective alternative to in‐person evaluations 16–25 . Overall, in the context of the COVID‐19 emergency, the improvement of RM coverage has facilitated continuous patient assistance and significantly reduced the risk of virus transmission among both more vulnerable populations and healthcare providers 26–28 …”
Section: Discussionmentioning
confidence: 97%
“…Owing to the wide range of accessible information, RM may contribute to the early detection of a wide range of arrhythmic manifestations, acute decompensation, and device‐related issues 5 . As reported in several studies, 8–13 RM not only plays a central role in preventing hospitalizations, improving survival and quality of life in patients with CIEDs, but is also a cost‐effective alternative to IPEs 14 …”
Section: Discussionmentioning
confidence: 98%
“…Mounting evidence has confirmed its usefulness for early detection of atrial and ventricular arrhythmias, as well as monitoring of system performance (e.g., lead failure and battery depletion 1–4 ). Additional benefits were also demonstrated among heart failure (HF) patients in terms of preventing unfavorable cardiovascular events and reducing hospital readmissions 5–9 . The outbreak of the novel severe acute respiratory syndrome coronavirus‐2 (SARS‐CoV‐2) forced a prompt reorganization of healthcare service delivery, mostly for nonurgent or nonemergent patients, including in‐office follow‐up appointments for patients with a CIED.…”
Section: Introductionmentioning
confidence: 99%
“…Chiu and coworkers recently showed that RM is noninferior to conventional in-hospital follow-up of heart failure patients implanted with a resynchronization device [ 10 ]. Thus, in a number of settings, RM can be beneficial without compromising patient safety, and in several studies, improved safety has actually been demonstrated [ 11 , 12 , 13 , 14 ].…”
Section: Safetymentioning
confidence: 99%